Seasonality’s Impact on Patients Receiving Intracytoplasmic Sperm Injections: A Reproductive Analysis - Fatimah A. Alzahrani; Zainab Al Hubil; Abdullrahman Mohammed Bawahab; Mamdoh Eskandar (Journal of Pharmacy and Bioallied Sciences)
Background: There is conflicting evidence regarding the impact of season on the assisted reproductive technology outcome. Therefore, this study aimed to retrospectively compare the outcomes of patients undergoing their first ICSI cycle, across four seasons in Aseer Region, Saudi Arabia. Methods: This study included 2,194 women who underwent their first intracytoplasmic sperm injection cycle in a private center in Abha City, Saudi Arabia during the period between January 2017 and September 2021. Women were divided according to the day of oocyte retrieval into Spring (n = 515), Summer (n = 583), Autumn (n = 589), and Winter (n = 503). Basal and stimulation characteristics were compared among the four study groups. Results: The age of participants ranged from 25 to 42 years (Mean ± SD: 34.72 ± 11.5 years). Fertilization rates were least during autumn, but highest during spring. In addition, live birth rates were least during summer and highest during autumn. However, all differences according to seasons were not statistically significant. Conclusion: Seasonality doesn’t affect pregnancy outcomes. The highest live birth rate in the autumn, and the lowest in summer. ICSI outcomes are consistent regardless of season, suggesting no need to consider seasonality in planning or performing ICSI.